Caracterización electroquímica de cuatro biomateriales metálicos de uso odontológico (2006)
ABSTRACT: The use of alloys with a minimum of 50% gold-content to minimize the potential of corrosion or galvanism in the implant- restoration interface has been suggested in the literature. However, long – term implications of placing two different kinds of metal at this level is still unknown. The purpose of this study was to perform the electrochemical characterization of four metallic biomaterials used in dentistry, to determine the possibility of corrosion among them when placed in contact during restorative procedures on implant fixtures. A prospective, descriptive, comparative, In - Vitro study was made for this purpose. Four types of metallic biomaterials were compared: commercially pure titanium using as a sample a Super CAT® implant (Lifecore Biomedical Inc., Chaska, MN); highly - noble alloy with a cast made from an UCLA abutment (Lifecore Biomedical Inc., Chaska, MN) with an IPS d.sing® 91 alloy (Williams, Ivoclar Vivadent AG, Liechtenstein); metal-base alloy with a cast made from an UCLA abutment with an IPS d.sing® 15 alloy; titanium alloy (Ti6Al4V) using a Lifecore COC® prosthetic abutment. The electrochemical characterization was made using a Bas Zahner potentiostat, with a three – electrode setup, obtaining three polarization curves for each group in its passive and non passive forms. The results showed that the titanium alloy had the best electrochemical behavior in both passive and non-passive state, which led to the smallest passive currents. The lowest corrosion potential was obtained for the metal-base alloy, because it had the highest passive currents.